1992
DOI: 10.1182/blood.v79.8.2034.2034
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring "mini-intensity" anticoagulation with warfarin: comparison of the prothrombin time using a sensitive thromboplastin with prothrombin fragment F1+2 levels

Abstract: Treatment with warfarin using a target International Normalized Ratio (INR) range of 1.7 to 2.5 is efficacious for many clinical indications, but the minimal intensity of anticoagulation required for antithrombotic protection has yet to be determined. To evaluate whether patients could be reliably monitored with a less intense regimen, we anticoagulated patients with warfarin for several months using a target INR range of 1.3 to 1.6 as determined by prothrombin time (PT) using a sensitive thromboplastin (Dade … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…The determination of TAT and FPA enables a direct estimate of the actual thrombin and fibrin generation in vivo. The general relevance is supported by their continuous increase with age and progressive atherosclerosis Hursting et al, 1993), their higher levels in the so-called prethrombotic states Bauer & Rosenberg, 1989;Bremme et al, 1992;Mannucci et al, 1992) and their suppression by anticoagulation therapy (Conway et al, 1987;Millenson et al, 1992). It may be interesting to assess the relevance of the data by comparing the relative increases in our patients with the ones found in prethrombotic states and overt thrombosis.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The determination of TAT and FPA enables a direct estimate of the actual thrombin and fibrin generation in vivo. The general relevance is supported by their continuous increase with age and progressive atherosclerosis Hursting et al, 1993), their higher levels in the so-called prethrombotic states Bauer & Rosenberg, 1989;Bremme et al, 1992;Mannucci et al, 1992) and their suppression by anticoagulation therapy (Conway et al, 1987;Millenson et al, 1992). It may be interesting to assess the relevance of the data by comparing the relative increases in our patients with the ones found in prethrombotic states and overt thrombosis.…”
Section: Discussionmentioning
confidence: 72%
“…3-1 . 6 (Millenson et al, 1992) in the steady state and a gradual withdrawal over 3 weeks may approach this situation. These data collectively suggest that tapering the anticoagulant dose may efficiently suppress the biochemical rebound.…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been reported that warfarin, adjusted to an INR of 1AE6-2AE2 in 43 patients with atrial fibrillation, lowered median d-dimer levels by 50%, whereas neither aspirin nor a fixed dose of warfarin of 1 mg/d (which has minimal effect on INR) had any effect (Lip et al, 1996). In another study of 21 patients with a history of stroke, low-intensity warfarin, target INR 1AE3-1AE6, lowered F1AE2 levels by 50% (Millenson et al, 1992). The current findings for both d-dimer and F1AE2 confirm and extend these earlier observations in a larger study of men at risk of coronary events.…”
Section: Discussionmentioning
confidence: 92%
“…Only a few reports include repetitive assays of markers conducted over several time points [2][3][4]. Perhaps only the changes from baseline should be reported, as in Millenson et al [5] and Koefoed et al [6], very few studies ask how clearly separated are the results from either untreated controls or from baseline. To be useful, there should be clear biologically meaningful differences in the results when reporting upon these markers.…”
Section: Introductionmentioning
confidence: 99%